Temperatur, Warna Nyala Api, dan Tinggi Api pada Pembakaran Premixed Bioetanol dari Lontar (Borassus Flabellifer) - Tobe, Adi Y.; Riwu, Defmit B.N.; Pah, Jack C.A.; Adoe, Dominggus G. H.; Baitanu, Rivanto (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
Bioethanol is a renewable energy that can be used as an alternative fuel. Bioethanol is alcohol produced from plants by using microorganisms through a fermentation process. This study aims to determine and analyze the combustion characteristics of premixed bioethanol from Lontar (Borassus Flabellifer), including: temperature, flame height and flame color. The research method uses a variety of air to be inserted, starting from 0 ml/min air flow to blow off in multiples of 50 ml/min. From the results of research that has been done, it shows that in premixed combustion the more air volume is given, the more blue the color of the flame will be, the temperature of the fire will increase and the height of the fire will be lower